Coordinated observations of sprites and in‐cloud lightning flash structure. Issue 12 (26th June 2013) - Lu, Gaopeng; Cummer, Steven A.; Li, Jingbo; Zigoneanu, Lucian; Lyons, Walter A.; Stanley, Mark A.; Rison, William; Krehbiel, Paul R.; Edens, Harald E.; Thomas, Ronald J.; Beasley, William H.; Weiss, Stephanie A.; et al.
Abstract : [1] The temporal and spatial development of sprite‐producing lightning flashes is examined with coordinated observations over an asymmetric mesoscale convective system (MCS) on 29 June 2011 near the Oklahoma Lightning Mapping Array (LMA). Sprites produced by a total of 26 lightning flashes were observed simultaneously on video from Bennett, Colorado and Hawley, Texas, enabling a triangulation of sprites in comparison with temporal development of parent lightning (in particular, negatively charged stepped leaders) in three‐dimensional space. In general, prompt sprites produced within 20 ms after the causative stroke are less horizontally displaced (typically <30 km) from the ground stroke than delayed sprites, which usually occur over 40 ms after the stroke with significant lateral offsets (>30 km). However, both prompt and delayed sprites are usually centered within 30 km of the geometric center of relevant LMA sources (with affinity to negative stepped leaders) during the prior 100 ms interval. Multiple sprites appearing as dancing/jumping events associated with a single lightning flash could be produced either by distinct strokes of the flash, by a single stroke through a series of current surges superposed on an intense continuing current, or by both. Our observations imply that sprites elongated in one direction are sometimes linked to in‐cloud leader structure with the same elongation, and sprites that were more symmetric were produced above the progression of multiple negative leaders. This suggests that the large‐scale structure of sprites could be affected by the in‐cloud geometry of positive charge removal. Based on an expanded dataset of 39 sprite‐parent flashes by including more sprites recorded by one single camera over the same MCS, the altitude (above mean sea level, MSL) of positively charged cloud region tapped by sprite‐producing strokes declined gradually from 10 km MSL (−35°C) to around 6 km MSL (−10°C) as the MCS evolved through the mature stage. On average, the positive charge removal by causative strokes of sprites observed on 29 June is centered at 3.6 km above the freezing level or at 7.9 km above ground level. Key Points: Triangulated sprites with lightning structure shown by the LMA. Spatial correlation between sprite, parent stroke, and in‐cloud negative leader. Significant variation of positive charge reservoir for sprite production.